Practical influence of the strategic process in organizational results - Menegon, Elizangela Maria Pas; Bernardi, Esmael Rossetto; dos Reis, Júlio Adriano Ferreira; Poli, Odilon Luiz; Menegon, Rodrigo (Revista de Negócios, 2018)
This article proposes to verify to what extent the practice of the strategic process exerts influence in the managerial results of a garment industry of the State of Santa Catarina. The topic is discussed theoretically, however, doubts remain about the effectiveness of its purposes with the daily execution of its activities. From this premise came the question of research: in what way does the practice of the strategic process influence the organizational results of a garment industry? It presents an exploratory-descriptive approach of qualitative nature, based on the methodology of case study. Initially, a bibliographical research was done to survey the theoretical aspects about the theme. In the empirical research, an interview with the director of the company was carried out, as well as a questionnaire was elaborated applied to the responsible managers of each area. The collected data were transcribed, analyzed and refined in order to generate information relevant to the study. As a result, it was possible to verify the importance of establishing strategic processes in practice and the synergy between those involved in decision making. It also demonstrates that the use of management tools enables a clearer understanding of all the strategic processes that it influences. In addition, it helps to predict risks, analyzes opportunities and provides an improved observation of the results and ends with the proposal of future studies.